A bilayer swellable drug-eluting ureteric stent: Localized drug delivery to treat urothelial diseases. (May 2018) - Lim, Wei Shan; Chen, Kenneth; Chong, Tsung Wen; Xiong, Gordon Minru; Birch, William R.; Pan, Jisheng; Lee, Bae Hoon; Er, Pei Shan; Salvekar, Abhijit Vijay; Venkatraman, Subbu S.; Huang, Yingying
Abstract: A bilayer swellable drug-eluting ureteric stent (BSDEUS) is engineered and implemented, as a sustained drug delivery platform technology that enhances localized drug delivery to the highly impermeable urothelium, for the treatment of urothelial diseases such as strictures and carcinomas. On deployment, the device swells to co-apt with the ureteric wall and ensure drug availability to these tissues. BSDEUS consists of a stent spray-coated with a polymeric drug containing polylactic acid-co-caprolactone (PLC) layer which is overlaid by a swellable polyethylene glycol diacrylate (PEGDA) based hydrogel. In-vitro quantification of released drug demonstrated a tunable time-profile, indicating sustained delivery over 1-month. The PEGDA hydrogel overlayer enhanced drug release and transport into explanted porcine ureteric tissues ex-vivo, under a simulated dynamic fluid flow. A preliminary pilot in-vivo feasibility study, in a porcine model, demonstrated that the swollen hydrogel co-apts with the urothelium and thus enables localized drug delivery to the target tissue section. Kidney functions remained unaffected and device did not result in either hydronephrosis or systemic toxicity. This successful engineering of a bilayer coated stent prototype, demonstrates its feasibility, thus offering a unique solution for drug-based urological therapy.